Optimal Pricing to Retard Entry - Lippman, Steven A. (Review of Economic Studies, 1980)
Journal Article Optimal Pricing to Retard Entry Get access Steven A. Lippman Steven A. Lippman University of California, Los Angeles Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 47, Issue 4, July 1980, Pages 723–731, https://doi.org/10.2307/2296938 Published: 01 July 1980 Article history Received: 01 December 1977 Accepted: 01 September 1979 Published: 01 July 1980